PENGARUH LATIHAN QUICK LEAP TERHADAP POWER OTOT TUNGKAI PADA TIM BOLAVOLI PUTRA SMA NEGERI DUA BANTAN - Muhammad Suhairi; Ramadi Ramadi; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Based on the observations that the author made on the men's volleyball team at SMA Negeri Dua Bantan during training and during the competition, the author looked at and encountered several problems, namely: Less maximal when making a leap to hit the ball above the net, less jump when performing service and the maximum leap when conducting this Research Block was held at the Bantan State High School two Jln. Budi luhur sukamaju Bengkalis This research was conducted from October to March 2019. With the implementation of 3 meetings a week. Whereas, the preetest and posttest were carried out before the exercise and after the quick leap (quick leap) exercise. To overcome this problem, a number of exercises were given so that in the future students could perform and play much better and most importantly after the athlete's limb muscle explosive training was given increased from before in order to be able to balance the opponent's game and achieve maximum achievement in the future. The design of this study was a pre-test posttest one group design that began with the Pree-test vertical power jump. After that the sample is given a quick leap (quick leap) training program for 16 meetings. After that, the Posttest vertical power jump is done. Based on the results of the pree test and post tets data analysis then the t test resulted in a Tcount of 10.66 and Ttable 1.796. It means that Tcount> Ttable can be summarized as follows: There is a significant effect between Quick Leap (Quick Leap) (X) Exercise and Leg Muscle Power (Y) on the volleyball team of the Bantan National High School.Key Words: Quick Leap, Power of Leg Muscles